Oral health status, oral health behavior, and frailty: A cross-sectional study - Mizuki Saito; Yoshihiro Shimazaki; Toshiya Nonoyama; Yoshinori Inamoto (Archives of Gerontology and Geriatrics Plus)
Background: There is an association between oral health and frailty, implying that tooth loss and periodontal disease increase the risk of frailty. To examine the association between oral health status and behaviors and frailty in individuals aged ≥ 75 years. Methods: A total of 7,927 participants underwent oral health examinations at the ages of 75, 77, and 80 years. The questionnaire for medical checkup of old-old (QMCOO) was used to assess frailty. Modified Poisson regression analysis was performed, with frailty as the dependent variable and family dentist, regular dental checkups, number of teeth, periodontal status, and swallowing function as independent variables. Modified Poisson regression analyses were conducted using the presence or absence of nine QMCOO domains (excluding smoking) as dependent variables. Results: Participants with a family dentist, those who underwent regular dental checkups, and those with a greater number of teeth had significantly lower relative risks (RRs) for frailty, with RRs of 0.72 [95 % confidence interval (CI): 0.59–0.89], 0.70 (95 % CI: 0.63–0.79), and 0.97 (95 % CI: 0.96–0.98), respectively. By contrast, individuals with periodontal pockets ≥ 6 mm and those with reduced swallowing function had significantly higher RRs for frailty [1.17 (95 % CI: 1.01–1.36) and 1.94 (95 % CI: 1.57–2.40), respectively]. Oral health status and behavior were also associated with QMCOO domains. Conclusion: Older individuals with good oral health had a lower likelihood of frailty. Regular oral care provided by a family dentist can reduce some of the negative effects of aging.